2019
DOI: 10.1111/jop.12925
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical assessment of chromatin licensing and DNA replication factor 1, geminin, and γ‐H2A.X in oral epithelial precursor lesions and squamous cell carcinoma

Abstract: Background Carcinogenesis occurs when the cell cycle is compromised. Chromatin licensing and DNA replication factor 1, geminin, and γ‐H2A histone family member X are expressed in cells in G1 phase, S/G2/M phases, and apoptosis, respectively, and these three markers may be useful for histological evaluation of malignant lesions. Here, we aimed to identify cell cycle phases and apoptosis using immunohistochemistry in oral epithelial precursor lesions and oral squamous cell carcinoma. Methods Chromatin licensing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…CDT1 has recently been reported to play an important role in human carcinogenesis. ( 10 12 ) It has also been reported that the expression of CDT1 is associated with the long-term prognosis of cancers, such as breast cancer, ovarian cancer and HCC. ( 13 15 ) However, to date, there have been no reports of the serial observation of changes in the extent of POAH and CDT1 expression in the livers of animals treated with experimental chemical carcinogens.…”
Section: Introductionmentioning
confidence: 99%
“…CDT1 has recently been reported to play an important role in human carcinogenesis. ( 10 12 ) It has also been reported that the expression of CDT1 is associated with the long-term prognosis of cancers, such as breast cancer, ovarian cancer and HCC. ( 13 15 ) However, to date, there have been no reports of the serial observation of changes in the extent of POAH and CDT1 expression in the livers of animals treated with experimental chemical carcinogens.…”
Section: Introductionmentioning
confidence: 99%
“…There is a link between the proportion of Ki67+ malignant cells and patient survival. Meanwhile, in Siril, et al in [18], the same discovery was reported. The prickle cell layer of oral squamous cell carcinoma expressed chromosome licensing and DNA replication factor 1.…”
Section: Immunohistochemical Examination With Cytokeratin Antibodies ...mentioning
confidence: 67%
“…MCM2 and Ki67 expression is constant across all cell-cycle phases (G1, S, G2, and M). However, Ki67 is only expressed in proliferating cells, whereas MCM2 may be expressed in non-proliferating cells during the G0 phase [16,17,18].…”
Section: Immunohistochemical Examination With Cytokeratin Antibodies ...mentioning
confidence: 99%
“…Although GMNN is transcriptionally regulated by E2F family members, the mechanism by which geminin modulates E2F-mediated transcriptional regulation of the GMNN gene is not fully understood (10). Geminin ablation has been reported to enhance colon and lung carcinogenesis (4) while it has also been found to be overexpressed in several human cancers including colon, rectal, oral and breast cancer (11)(12)(13).…”
mentioning
confidence: 99%